Private prison labour: paradox or possibility? Evaluating modern-day systems and establishing a model framework through the lens of the Forced Labour Convention - Mario Guido (UCL Journal of Law and Jurisprudence, 2019)
To download this paper please click https://discovery.ucl.ac.uk/id/eprint/10086914 Overcrowding, deteriorating conditions, ever-increasing costs, recidivism. These are the terms that come to mind when thinking of the world’s punitive justice systems. Ostensibly, the international community has set out to combat these issues and it would be incorrect to say that measures in that direction have not been taken. Nonetheless, certain states have sought to remedy reoffending and favour reinsertion by increasing employment opportunities for prisoners and delegating the task to the private sector. In some common law jurisdictions, prisons have been entirely privatised (‘wholesale’ approach) whereas civil law jurisdictions tend to only privatise specific services while custodial functions remain with the State (‘semi-privée’ system). Regardless, given that France, Germany, and Australia have adopted these practices despite adoption of the Forced Labour Convention of the International Labour Organisation, which prima facie precludes private prison labour, it is thus necessary to analyse the reasons for these developments and to evaluate these systems. This article identifies the French system as the most compatible with the Convention and proposes a model framework that complies with the norm and serves the objectives of modern penal systems.